Evaluation of Drug Toxicity for DNA Vaccine Candidates Against Infectious Diseases: Hepatitis C as Experimental Model - Bacardí, Dania; Cosme, Karelia; Suárez, José; Amador-Cañizares, Yalena; Dueñas-Carrera, Santiago (IntechOpen, 2012)
None